2019
DOI: 10.17239/l1esll-2019.19.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Key elements of L1-oral language teaching and learning in secondary education. A literature review

Abstract: In order to inform the redesign of L1-oral language education in secondary schools, international literature was analyzed to deduce key elements, effective and practical ingredients, of good quality L1-oral language lessons. Thirteen articles were selected based on a systematic database search and analyzed with Van den Akker's curricular spiderweb (Thijs & Van den Akker, 2009). From the most frequently mentioned codes we could extract five, empirical based, key elements which support student oral language lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…When comparing the findings of the present work with the key elements for good-quality oracy L1 education (Wurth et al, 2019, p. 18), a clear oral language skills framework with criteria seems to be lacking, which would have assisted the teachers in increasing their metacognitive awareness (Mercer et al, 2017). The exploration and assessment of students' speaking abilities were important for teachers, and these abilities should be assessed regularly, according to Wurth et al (2019). However, the Norwegian teachers found it challenging because of time constraints.…”
Section: Summing Teachers' Norm Sources and Prerequisitesmentioning
confidence: 81%
See 1 more Smart Citation
“…When comparing the findings of the present work with the key elements for good-quality oracy L1 education (Wurth et al, 2019, p. 18), a clear oral language skills framework with criteria seems to be lacking, which would have assisted the teachers in increasing their metacognitive awareness (Mercer et al, 2017). The exploration and assessment of students' speaking abilities were important for teachers, and these abilities should be assessed regularly, according to Wurth et al (2019). However, the Norwegian teachers found it challenging because of time constraints.…”
Section: Summing Teachers' Norm Sources and Prerequisitesmentioning
confidence: 81%
“…"Self-, peer, and teacher feedback" on speaking is crucial (Wurth et al, 2019, p. 18) and is part of the Norwegian teachers' assessment repertoire (Table 3). Observations of and discussions about videotaped speakers are also vital in oracy education (Wurth et al, 2019) and seem to be an untapped resource among these participants. However, the students did send in mobile film recordings of their oral presentations for the teacher's assessment (Table 3).…”
Section: Summing Teachers' Norm Sources and Prerequisitesmentioning
confidence: 99%
“…En la línea de estudios recientes que abordan la enseñanza y el aprendizaje de la lengua oral en L1 en Educación Secundaria (para una revisión ver Wurth et al, 2019), la segunda pregunta de investigación que ha dirigido este trabajo está relacionada con la percepción que tiene el profesorado sobre la mejora de la competencia oral de su alumnado a través del uso de la EVALOE-SSD. A juicio del profesorado, su uso ha contribuido a la mejora de la competencia oral del alumnado, tal y como se recoge en las valoraciones.…”
Section: Discussionunclassified
“…In a literature review of research on oral language in MS, Wurth et al [ 81 ] found that, despite the long tradition of teaching public speaking in education, little research attention was paid to oral competence in MS, and few studies examined the practical or affective aspects of oral language teaching in formal contexts. The above study and some of the others reviewed (e.g., [ 82 , 83 ]) highlighted the need to gain a better understanding of how spoken language is being taught and learnt at this stage of education.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the relationship between the TSOC scores and EI and metacomprehension not only provides the instrument with good evidence of construct validity, but also enables us to theorize about the relationships that exist between these three important variables for academic performance. The study by Wurth et al [ 81 ] introduced the possibility of determining the existence of causal relationships between regular oral language practice and self-confidence [ 82 , 88 , 92 , 93 , 94 ]. In our study, we also found significant correlations between competences traditionally associated with oral language, such as emotional intelligence and the self-regulation of reading comprehension.…”
Section: Discussionmentioning
confidence: 99%